Breast Oncology: Techniques, Indications, and Interpretation - Heller, Samantha L.; Moy, Linda; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents up to date debates and issues in the world of breast MRI with a very practical focus on how to incorporate current understanding of breast MRI into clinical practice. The book is divided into three key sections, all of which have critical impact for the breast imager: 'Techniques', 'Indications', and 'MRI Findings, Interpretation, and Management', which also incorporates a focus on key management dilemmas, including appropriate follow-up intervals for benign findings on MRI and management of probably benign lesions. Breast Oncology: Techniques, Indications, and Interpretation is written by expert researchers and specialist clinicians, to ensure the reader is exposed to in-depth and current understanding of the issues relevant to best clinical MRI breast practice. .
Section 1. Techniques -- 1. Breast MRI Technique -- 2. Breast MRI: Standing Terminologies and Reporting -- Section 2. Indications -- 3. MRI and Screening -- 4. MRI and Preoperative Staging in Women Newly Diagnosed with Breast Cancer -- 5. Magnetic Resonance Imaging and Noeadjuvent Chemotherapy -- 6. Breast MRI and Implants -- 7. Problem Solving Breast MRI for Mammographic, Sonographic, or Clinical Findings -- 8. Post-Operative findings/recurrent disease -- Section 3. MRI Findings, Interpretation and Management -- 9. In Situ Disease on Breast MRI -- 10. MRI appearance of Invasive Breast Cancer -- 11. Targeted Ultrasound after MRI -- 12. Breast Biopsy and Breast MRI Wire Localization -- 13. Breast MRI and the Benign Breast Biopsy -- 14. BI-RADS 3 Lesions on MRI -- 15. Multiparametric Imaging: Cutting-Edge Sequences and Techniques including Diffusion-Weighted Imaging, Magnetic Resonance Spectroscopy, and PET/CT or PET/MRI -- 16. Abbreviated Breast MRI -- 17. Personalized Medicine, Biomarkers of Risk and Breast MRI.
Keywords: Medicine; Radiology; Oncology; Medicine & Public Health; Oncology; Diagnostic Radiology